REGRESSION AND STABILITY ANALYSES OF VARIOUS FLOW AND HEAT TRANSFER PROBLEMS WITH PASSIVE CONTROL OF NANOPARTICLES IN NANOFLUIDS - JAHAN, SHAH (2018)
In this study, the regression and stability analysis of various flow and heat transfer problems with passive control of nanoparticles in nanofluids along with various physical aspects are carried out. Specific problems revolve around the study, unsteady, two-dimensional, three-dimensional, vertical throughflow, linear, nonlinear permeable stretching/shrinking sheet and moving plate while the thermal condition is the convective heating.